2020
DOI: 10.1111/jfpp.14913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some fermentation conditions on antibacterial activity of fermented milk by kefir grains

Abstract: Probiotics may be a single strain or a set of different microorganisms. Kefir is an example of a probiotic that contains various types of bacteria and yeasts (Prado et al., 2015). Kefir beverage is one of the oldest fermented milk products, a natural probiotic and alcohol-lactic beverage derived from milk fermentation by kefir grains. Kefir is effective in promoting health, boosting the immune system, balancing blood pressure, treating gastrointestinal diseases, and lowering serum cholesterol levels. It also h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Etawa goat milk pasteurized is taken in as much as 1 L and added with 10% kefir seeds. The kefir milk is fermented at 37 °C for 48 h [17].…”
Section: Etawa Goat Milk Kefir Productionmentioning
confidence: 99%
“…Etawa goat milk pasteurized is taken in as much as 1 L and added with 10% kefir seeds. The kefir milk is fermented at 37 °C for 48 h [17].…”
Section: Etawa Goat Milk Kefir Productionmentioning
confidence: 99%
“…Many parameters could affect the final antimicrobial activity of kefir. First, the type of milk substrate could affect the antibacterial activity of kefir samples [45]. The fatty acid composition and lactose content could affect the product's final pH and acid content, in addition to the kinds of peptides and other substances that make up the bioactive substances.…”
Section: Anti-microbial Activitymentioning
confidence: 99%
“…Hence, it can be construed that the anti-bacterial action of kefir is influenced by distinct components produced at fermentation at different stages, resulting in a varied anti-microbial pattern as a function of time [44]. In another study, 48 hours and 72 hours of fermented kefir samples showed higher anti-bacterial activity against E. coli and S. aureus, respectively [45]. Thus, the shorter fermentation time (24 hours) in this study, when compared to earlier studies, might be the reason for the partial inhibition of bacteria (smaller zone of inhibition).…”
Section: Anti-microbial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its antibacterial, antifungal and antitumor activities, kefir is effective in improving health, strengthening the immune system, balancing blood pressure and lowering serum cholesterol levels. (Ajam and Koohsari 2020). Therefore, there is a need for the development of natural antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%